Determining the onset and cessation of seasonal rains in Shire Valley, Southern Malawi - Valle, Mercy (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Malawi's agricultural activities rely heavily on rainfall. Rain signals the start of a distribution of rain that is unsuitable for plant development, whereas lighting marks the end of rain's ability to support plants. Malawi's tropical savanna climate has a rainy season from November to April, accounting for 95% of total annual rainfall, and a dry season from May to October, with milder temperatures and occasional showers at higher elevations from May to July. Methods: This study examines the commencement and cessation of seasonal rainfall in the Shire Valley, southern Malawi, between 1990 and 2019. The objectives include identifying rainfall characteristics, examining trends in the start, closure, and length of the rainy season, and categorizing onset and narrative dates. The Department of Climate Change and Meteorological Services provided daily rainfall data, and dates were determined using R-Instat. Findings: Rain often begins in Nsanje on November 28, followed by Ngabu on December 7, and Nchalo on December 9. The advertising dates are comparable across stations: April 3 for Nchalo and Ngabu, and April 5 for Nsanje. While most years fall within the typical range, global phenomena like La Niña and El Niño can cause early or late results. Conclusion: These insights are crucial for sustainably managing and developing socioeconomic activities at the national and district levels in Malawi. Novelty/Originality of this Study: This study provides a comprehensive analysis of the onset and cessation dates of the rainy season, utilizing long-term rainfall data spanning from 1990 to 2019. This localized analysis addresses existing gaps in the understanding of regional rainfall characteristics, which is essential for enhancing agricultural planning and mitigating resource wastage in an area heavily reliant on rain-fed agriculture.